2016
DOI: 10.3892/or.2016.5030
|View full text |Cite
|
Sign up to set email alerts
|

PRL-3 promotes the peritoneal metastasis of gastric cancer through the PI3K/Akt signaling pathway by regulating PTEN

Abstract: Peritoneal metastasis is the most frequent cause of death in patients with advanced gastric carcinoma (GC). The phosphatase of regenerating liver-3 (PRL-3) is recognized as an oncogene and plays an important role in GC peritoneal metastasis. However, the mechanism of how PRL-3 regulates GC invasion and metastasis is unknown. In the present study, we found that PRL-3 presented with high expression in GC with peritoneal metastasis, but phosphatase and tensin homologue (PTEN) was weakly expressed. The p-PTEN/PTEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…Function of the PTEN/PI3K/Akt pathway in GC. PI3K signaling is vital in regulating multiple fundamental cellular activities, including cell proliferation, apoptosis and metastasis (49). With frequent alterations identified in GC, the PTEN/PI3K/Akt pathway is significantly involved in gastric carcinogenesis and progression (11,50).…”
Section: Genetic Alterations Of the Pten/pi3k/akt Pathway In Gcmentioning
confidence: 99%
“…Function of the PTEN/PI3K/Akt pathway in GC. PI3K signaling is vital in regulating multiple fundamental cellular activities, including cell proliferation, apoptosis and metastasis (49). With frequent alterations identified in GC, the PTEN/PI3K/Akt pathway is significantly involved in gastric carcinogenesis and progression (11,50).…”
Section: Genetic Alterations Of the Pten/pi3k/akt Pathway In Gcmentioning
confidence: 99%
“…Further methods to externally increase MMP activity include mechanical induction to replicate a more rigid ECM[224], injection of MMP regulators[225], gene delivery[226], or oxidative stress[227]. Curiously, mechanical induction of MMP overexpression in MDA-MB-231 cells was correlated with advanced resistance to free drug chemotherapeutics, but was not tested against MMP-induced controlled release systems[224].…”
Section: Strategies For Targetingmentioning
confidence: 99%
“…It was reported that downregulation of PTEN was correlated with peritoneal recurrence in GC, 13,14 which was associated with the activation of the PI3K/AKT pathway. 13 In renal cell carcinoma, 15 patients with bone metastasis were reported to have lower PTEN expression than those without. Bone metastasis might be caused by AKT and integrin a5 signaling.…”
Section: Discussionmentioning
confidence: 97%
“…The conclusion might not be reliable, although the statistical value is considerable. However, few studies 13,14 investigated the correlation between PTEN expression and recurrence pattern in GC, and the patient number enrolled is limited; this study enrolled the largest population to date to investigate their relationship. The enrollment of more patients is required to verify our findings in the future.…”
Section: Discussionmentioning
confidence: 99%